Iodine Intake, UIE Levels, Nutritional Status and Academic Achievements in School-Age Children in Magelang, Central Java - Romiza Arika (Universitas Islam Negeri Sumatera Utara, Medan, 2022)
Iodine deficiency in school children is estimated at 25% worldwide. Complete brain development occurs at the age of 7 years and the development of cognitive function can be increased until 15 years with normally iodine status, namely adequate intake of iodine and Urinary Iodine Excretion (UIE). This study aims to analyze the relationship between iodine intake, UIE, height for age and academic achievements in school-age children. This research was an analytic observational study with a cross sectional design. This research was conducted in 4 elementary schools in Pakis District in March 2019. The samples were selected by random sampling, totaling 177 subjects. The dependent variable was the school's academic achievements in the form of midterm exam scores for maths, arts and sports. While the independent variables were iodine intake, UIE and height for age. The assessment of iodine intake was using a 24-hour recall form and interpreted using the 2007 Nutrisurvey application. The analysis method for UIE is the acid digestion method. Height for age is a child's nutritional status that can be determined based on anthropometric measurements. Academic achievements is learning outcomes as measured by midterm exam scores iin maths, arts, culture and sports. Data was analyzed by Linear Regression. Iodine intake increased math (b=0.01; p=0.014), art and sport (b=0.03; p=<0.001) scores. UIE levels increased math (b=0.01; p=0.001), art (b=0.01; p=0.002) and sport (b=0.01; p=0.003) scores. Height for age increased sport scores (b=1.58; p=0.010). The conclusion of this study is that height for age increase sports ability and iodine intake also UIE can increase academic achievements. Keyword: Academic Achievements, Height for Age, Iodine Intake, UIE